2003
DOI: 10.1128/iai.71.3.1337-1342.2003
|View full text |Cite
|
Sign up to set email alerts
|

Localized Eosinophil Degranulation Mediates Disease in Tropical Pulmonary Eosinophilia

Abstract: To explore the mechanisms underlying the eosinophil-mediated inflammation of tropical pulmonary eosinophilia (TPE), bronchoalveolar lavage (BAL) fluid, serum, and supernatants from pulmonary and blood leukocytes (WBC) from patients with acute TPE (n ‫؍‬ 6) were compared with those obtained from healthy uninfected individuals (n ‫؍‬ 4) and from patients with asthma (n ‫؍‬ 4) or elephantiasis (n ‫؍‬ 5). Although there were no significant differences in the levels of interleukin-4 (IL-4), IL-5, IL-13, eotaxin, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In contrast, this marked increase in the Th2-associated IgE levels and eosinophilia driven by filarial antigens in Fil + A + patients has also been implicated in the pathogenesis of some syndromes associated with filarial infections (6770) including tropical pulmonary eosinophilia (TPE) (68, 71, 72) and the localized hyperreactive dermatitis (sowda) seen in Onchocerca volvulus -infected patients (7375). Finally, given that IL-10-mediated modulation of Th1/Th2/Th17/Th9 responses (76) has been associated with clinically asymptomatic filarial infection, it is possible that allergic sensitization coincident with these filarial infections results in altering the balance of regulatory and effector responses that could in turn alter the longevity of the parasites in their human hosts.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this marked increase in the Th2-associated IgE levels and eosinophilia driven by filarial antigens in Fil + A + patients has also been implicated in the pathogenesis of some syndromes associated with filarial infections (6770) including tropical pulmonary eosinophilia (TPE) (68, 71, 72) and the localized hyperreactive dermatitis (sowda) seen in Onchocerca volvulus -infected patients (7375). Finally, given that IL-10-mediated modulation of Th1/Th2/Th17/Th9 responses (76) has been associated with clinically asymptomatic filarial infection, it is possible that allergic sensitization coincident with these filarial infections results in altering the balance of regulatory and effector responses that could in turn alter the longevity of the parasites in their human hosts.…”
Section: Discussionmentioning
confidence: 99%
“…These are then ingested by mosquitos taking blood meals, followed by subsequent maturation to thirdstage larvae, completing the life cycle of the organism (126). The pathogenesis of TFPE has not been clarified fully, but a strong eosinophilic immunologic response to microfilariae trapped in the lungs likely plays a pivotal role (129,145,202). Interestingly, only a small percentage of patients affected with lymphatic filariasis develop pulmonary manifestations, and there is a strong male predominance in developing TFPE (126,207).…”
Section: Tfpementioning
confidence: 99%
“…These cases further underscore the necessity of early intervention, because chronic TPE may result in permanent, irreversible deficits in pulmonary function, despite treatment with diethylcarbamazine [14]. In fact, it has recently been shown that pulmonary eosinophils in TPE degranulate and release toxic oxygen radicals long after treatment with diethylcarbamazine [19], increasing damage initiated during the acute stages of disease. When TPE is recognized and treated early, patients often have a dramatic and rapid response to diethylcarbamazine.…”
Section: Discussionmentioning
confidence: 96%